The novelties of legal lien under the legislation of the Russian Federation - Olga Vladimirovna Efimova, Olga Vyacheslavovna Gridneva,; Vedysheva, Nataliya Olegovna; Tamara Vladimirovna Korchagina, Evgeniy Enkirovich Ryazanov, (Opción, 2019)
The study is based on the use of the system approach in combination with the comparative method. The use of the system approach allowed to consider the process of development of mortgage legal relations in close relationship with the state policy in this area.Summing up the results of the conducted research, it is necessary to note the following ideas. The introduction of new types of the pledge is caused not only by the expansion of the sphere of influence of civil law on public relations, but also by the introduction of new legal phenomena, such as corporate legal relations